TIAMAT: um framework para apoiar a integração de métodos de prospecção tecnológica - Barbosa, Carlos Eduardo (2018)
There are several organizations with Research and Development (R&D) sectors spread around the world, covering several research areas. There are a number of factors which led these organizations to be spread in several cities and countries: lower taxes, reduced research costs, the availability of qualified employees, and proximity to the region of interest are common reasons for companies researching outside their headquarters. Beyond such factors, innovation in different production process stages stimulated the creation of specialized research centers, which are also spread. Therefore, it becomes necessary to coordinate the collaboration of several researchers working in distributed R&D centers performing a Future-oriented Technology Analysis (FTA) – a set of methods focused in analyze the future of technologies and their impacts, used as organizational strategic planning tool. This work proposes an FTA framework for organizations, named TIAMAT, which performs strategic management of distributed R&D centers. TIAMAT‘s main contribution is the standardized FTA process inside the organization. The proposed framework was designed to be instanced in several types of organizations, public or private. TIAMAT was implemented and evaluated, supporting distributed FTA as designed.